Management of extensive subcutaneous emphysema using vacuum-assisted closure therapy - Dalia Sindi; Abdurrahman Mirza; Mohamed gharieb Khirallah; Nasir M. Bustangi (Elsevier, 2019)
Subcutaneous emphysema, pneumomediastinum, and pneumopericardium, are a spectrum of disorders, rare in children (1). literature incidence was 0.0025% for spontaneous pneumomediastinum among emergency department visits (2). We present a 7 years old came with a complaining of shortness of breath (SOB) with neck swelling and he was mildly distressed. CT scan showed right pneumothorax, pneumomediastinum, pneumopericardium and extensive subcutaneous emphysema. In the operating room (OR), intercostal chest tubes were inserted bilaterally and bilateral transverse sub-clavicular incisions connected to a vacuum assistant wound closure device (VAC). VAC was found to be effective technique in the management of a massive subcutaneous emphysema. Keywords: Pediatric, Subcutaneous emphysema, Vac